Facile construction of heterogeneous dual-ionic poly(ionic liquid)s for efficient and mild conversion of CO2 into cyclic carbonates - Xie, Guanqun; Qiu, Jiaxiang; Li, Huadeng; Luo, Hongbin; Li, Shuo; Zeng, Yanbin; Zheng, Ke; Wang, Xiaoxia (Journal of environmental sciences (China), 2025)
•Novel heterogeneous dual-ionic PILs were prepared from readily available starting materials.•The PILs exhibited excellent performance for CO2 cycloaddition with various epoxides under mild conditions.•The catalyst showed great recyclability and scale-up potential.•Key catalytic active sites were probed and a reasonable mechanism was proposed accordingly. In the context of peaking carbon dioxide emissions and carbon neutrality, development of feasible methods for converting CO2 into high value-added chemicals stands out as a hot subject. In this study, P[D+COO−][Br−][DBUH+], a series of novel heterogeneous dual-ionic poly(ionic liquid)s (PILs) were synthesized readily from 2-(dimethylamino) ethyl methacrylate (DMAEMA), bromo-substituted aliphatic acids, organic bases and divinylbenzene (DVB). The structures, compositions and morphologies were characterized or determined by nuclear magnetic resonance (NMR), thermal gravimetric analysis (TGA), infrared spectroscopy (IR), scanning electron microscopes (SEM), and Brunauer-Emmett-Teller analysis (BET), etc. Application of the P[D+COO−][Br−][DBUH+] series as catalysts in converting CO2 into cyclic carbonates showed that P[D+COO−][Br−][DBUH+]-2/1/0.6 was able to catalyze epiclorohydrin-CO2 cycloaddition the most efficiently. This afforded chloropropylene carbonate (CPC) in 98.4% yield with ≥ 99% selectivity in 24 hr under solvent- and additive-free conditions at atmospheric pressure. Reusability experiments showed that recycling of the catalyst 6 times only resulted in a slight decline in the catalytic performance. In addition, it could be used for the synthesis of a variety of differently substituted cyclic carbonates in good to excellent yields. Finally, key catalytic active sites were probed, and a reasonable mechanism was proposed accordingly. In summary, this work poses an efficient strategy for heterogenization of dual-ionic PILs and provides a mild and environmentally benign approach to the fixation and utilization of carbon dioxide. [Display omitted]